2015
DOI: 10.2478/raon-2014-0050
|View full text |Cite
|
Sign up to set email alerts
|

Febrile neutropenia in chemotherapy treated small-cell lung cancer patients

Abstract: Background.Chemotherapy with platinum agent and etoposide for small-cell lung cancer (SCLC) is supposed to be associated with intermediate risk (10–20%) of febrile neutropenia. Primary prophylaxis with granulocyte colony-stimulating factors (G-CSFs) is not routinely recommended by the treatment guidelines. However, in clinical practice febrile neutropenia is often observed with standard etoposide/platinum regimen. The aim of this analysis was to evaluate the frequency of neutropenia and febrile neutropenia in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…2,3 Fever remains the most prevalent and evident sign of infection in neutropenic cancer patients and early initiation of broad-spectrum antibiotic therapy significantly reduces mortality in these patients. 47 …”
Section: Introductionmentioning
confidence: 99%
“…2,3 Fever remains the most prevalent and evident sign of infection in neutropenic cancer patients and early initiation of broad-spectrum antibiotic therapy significantly reduces mortality in these patients. 47 …”
Section: Introductionmentioning
confidence: 99%
“…Kukec et al . showed that high plasma etoposide exposure was associated with both longer survival and increased severity of neutropenia in SCLC patients (4). Hence, the neutrophil blood count could be used as a surrogate of plasma drug exposure and therefore could be helpful to guide dosing optimization.…”
Section: Discussionmentioning
confidence: 99%
“…However, overall response rate (23%) and progression-free survival (5 months) remain disappointing. Furthermore, lower rates of severe hematological toxicities are observed with EDP-mitotane regimen than with platinum-etoposide in small-cell lung cancer (SCLC) patients (11 vs 53% of grade 3–4 neutropenia) (4). Since neutropenia is commonly associated with etoposide AUC (5), this may indicate a lower plasma etoposide exposure in ACC patients treated with mitotane.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the higher risk of febrile neutropenia with common regimens for SCLC compared with NSCLC makes the addition of G-CSFs appealing. Retrospective data from SCLC patients receiving standard treatment with cisplatin-etoposide suggest that, although the risk for febrile neutropenia is considered intermediate, it is still relevant and susceptible of significant benefit with primary prophylaxis [30]. Most clinical trials involving SCLC employed dose-dense or dose-intense regimens, and in general schedules characterized by high risk of febrile neutropenia, such as cyclophosphamidedoxorubicin-etoposide, cyclophosphamide-epirubicin-etoposide or vincristine-ifosfamide-carboplatinetoposide.…”
Section: Experience With Granulocyte Colonystimulating Factors In Lunmentioning
confidence: 97%